Non-canonical cyclic AMP SMAD1/5/8 signalling in human granulosa cells. (15th June 2019) - Bertoldo, M.J.; Cheung, M.Y.; Sia, Z.K.; Agapiou, D.; Corley, S.M.; Wilkins, M.R.; Richani, D.; Harrison, C.A.; Gilchrist, R.B.
Abstract: Development of mammalian ovarian follicles is promoted by the combined action of endocrine cues and paracrine factors. Follicle stimulating hormone (FSH), through the action of cAMP drives follicular growth and development. The oocyte secretes powerful growth factors such as bone morphogenetic protein 15 (BMP15) to regulate granulosa cell proliferation, metabolism, steroidogenesis and differentiation through the activation of SMAD1/5/8. This study investigated the role of the cAMP signalling pathway on SMAD1/5/8 action in human granulosa cells. Cyclic AMP enhanced BMP15-induction of a SMAD1/5/8-specific BRE reporter. Moreover, in the absence of BMP ligand, cAMP also activated SMAD1/5/8-induced BRE activity. Cyclic AMP increased canonical downstream targets of BMP signalling such as inhibitor of differentiation ( ID ) mRNA expression. The observed effects were not mediated by secretion of BMPs as cAMP did not promote BMP ligand mRNA expression and a BMP extracellular antagonist, the BMP type II receptor ectodomain, did not affect cAMP-induced ID mRNA expression. Finally, the ERK1/2 pathway was shown to be required for the maintenance of cAMP-induced SMAD1/5/8 activity. Together our results suggest a novel and non-canonical pathway for cAMP signalling in human granulosa cells. Cyclic AMP appears to promote SMAD1/5/8 pathway activity intracellularly and has the ability to activate canonical SMAD1/5/8 downstream targets. Our results add another layer of complexity to the interactions between endocrine signalling and oocyte-secreted BMP ligands during folliculogenesis. Given the importance of both cAMP and SMAD1/5/8 pathways in follicular development, these interactions are likely required for the fine-tuning of oocyte paracrine signalling by endocrine stimuli.